What are the gender, class and ethnicity of citizenship? A study of upper secondary school students' views on Citizenship Education in England and Sweden - Laila Nielsen; Ralph Leighton (Linköping University Electronic Press, 2017)
The purpose of this article is to examine and compare how the ethnicity, gender and social class conditions of citizenship influence, and are understood by, teachers and secondary school students in England and Sweden. The intention is also to compare how conditions of citizenship are dealt with in social studies for upper secondary school in England and Sweden. The relationship between students education and real conditions for citizenship is complex and partly differs between, as well as within, the two countries. The present comparative examination and analysis aims to visualize both specific and common conditions of citizenship in England and Sweden. This is to draw attention to how the meaning of frequently used terminology and images in the field of Citizenship Education do not always coincide with teachers' and students' own opinions and perceived meanings. By doing this we hope to contribute some new knowledge regarding one of the most difficult challenges that citizenship education is struggling with, whether the provided knowledge and values prepare todays youth to defend and develop future democratic and just societies. To achieve this, we have conducted a number of interviews with teachers and secondary school students and asked them about their experiences and opinions regarding Citizenship Education and the nature of citizenship. The following main questions were central to the interviews: What knowledge and skills does a citizen need in a democracy and how is the meaning of citizenship connected to gender, class and ethnicity? How are personal liberties affected by the citizen's gender, class and ethnicity according to the respondents? What are teachers' and students' experiences of Citizenship Education and how does school pay attention to citizens' conditions based on gender, class and ethnicity? In recent years, both public debate and published research have shown that, in order to understand the real meanings of citizenship, it is necessary to understand and interpret formal citizenship rights and responsibilities from individuals' social and cultural conditions as characterised by gender, ethnicity and social class. During the 2000s, the Swedish National Agency for Education (Skolverket) presented recurrent reports that shows how socio-economic background, in combination with foreign background, are crucial for pupils school results. The reports also show how segregation between schools and residential areas has increased on the basis of residents socio-economic and ethnic background. This group of students are a part of tomorrows citizens, which are also likely to remain marginalized even as adults. The links between Swedish school policy, pupils school results and the democratic development of society at large has been observed and analysed in contemporary Swedish research. In England, the picture is slightly different with the 7 per cent of the population who experience private education being over-represented in positions of power and influence. In May 2012, the then Secretary of State for Education Michael Gove provided a list of leaders in the arts, sciences, politics, sports, journalism, entertainment and other fields who had all been to independent schools, concluding that In England, the picture is slightly different with the 7 per cent of the population who experience private education being over-represented in positions of power and influence. In May 2012, the then Secretary of State for Education Michael Gove provided a list of leaders in the arts, sciences, politics, sports, journalism, entertainment and other fields who had all been to independent schools, concluding that "the sheer scale, the breadth and the depth, of private school dominance of our society points to a deep problem in our country . . . Those who are born poor are more likely to stay poor and those who inherit privilege are more likely to pass on privilege in England than in any comparable county." There is significant evidence that socio-economic background, in combination with ethnic background, continue to be highly influential on pupils school results. Links between national education policy, social class and pupils school results appear to remain entrenched in England. When we identify cultural and social conditions as in any way hindering the status of citizenship, we do so from a perspective which does not seek to blame the less powerful for holding particular cultural perceptions but which recognises the barriers a dominant culture sets against those with less power. The insight that tells us it is necessary to comprehend individuals' social and cultural conditions in order to understand and interpret their formal citizenship rights and responsibilities is not, however, particularly recent. Marx wrote over 160 years ago that, "if you assume a particular civil society ... you will get particular political conditions", from which it must follow that any society divided on the grounds of class, ethnicity and gender will present political conditions which reflect such divisions. It is also the case that there is likely to be a significant space between what is (the real) and what is perceived (the formal) just because there is inequality it does not follow that everyone is aware of that inequality.